Complications of Endonasal Odontoidectomy in Pediatric versus Adult Populations: A Systematic Review and Meta-Analysis - Kosaraju, Nikitha; Lee, Christine K.; Qian, Z. Jason; Fernandez-Miranda, Juan C.; Nayak, Jayakar V.; Chang, Michael T. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction Endonasal odontoidectomy (EO) is a procedure for addressing compressive pathology of the craniovertebral junction. While EO has been well established in adults, its complications and cervical fusion practices are less understood in pediatric patients, despite differences in sinonasal and craniocervical anatomy. This study summarizes and compares EO complications and need for cervical fusion in pediatric and adult patients.Methods This was a systematic review and meta-analysis. Literature review was conducted using PubMed, Web of Science, and Embase to identify studies reporting complications post-EO in adult and pediatric patients. Complications were categorized as neurologic, swallowing, or respiratory. Complication and posterior fusion rates were compared using a random-effects model.Results A total of 738 articles were identified, of which 28 studies including 307 adult cases and 22 pediatric cases met inclusion criteria for systematic qualitative and quantitative review. The rates for adult and pediatric cases, respectively, were: respiratory complications 13.4 versus 9.1%, swallowing complications 12.1 versus 4.5%, neurologic complications 8.5 versus 9.1%, and cervical fusion rates 73.3 versus 86.4%. Across eight studies qualifying for meta-analysis, there were no differences in cervical fusion (odds ratio [OR]: 0.5, 95% confidence interval [CI]: [0.1, 2.1]), respiratory complications (OR: 3.5, 95% CI: [0.8, 14.5]), or swallowing complications (OR: 3.5, 95% CI: [0.5, 26.0]); however, pediatric patients had a higher rate of neurologic complications (OR: 5.2, 95% CI: [1.1, 25.0]).Conclusion In EO, rates of aerodigestive complications and cervical fusion are similar in both populations. There may be an increased risk of neurologic complications in pediatric patients, although more high-quality studies are needed.
Keywords: endonasal odontoidectomy; craniocervical junction; pediatric; complications; posterior fusion